2016
DOI: 10.1108/bfj-05-2016-0193
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of short sea shipping: the case of olive oil industry

Abstract: Purpose - The purpose of this paper is to analyse the economic benefits of short sea shipping (SSS) in the shape of Motorways of the Sea (MoS) compared to road transport. The study cover a gap in agro-food economics and analyses the economic benefits of sea transport mode compared to road transport in the food trade between Spain and Italy for a specific product: olive oils. \ud \ud Design/methodology/approach - Three different transportation scenarios are considered (road only, road combined with accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…For road haulage, the generalized cost from Leige to Riga, St. Petersburg, and Tallinn is about 80, 105, and 97 (in euros per ton), respectively, while for SSS, the corresponding cost is 69, 101, and 79 euros per ton, respectively. In a similar study, Galati, et al [27] identified that from Jaen to main Italian cities, the unit cost for road haulage is between 0.14 to 0.20 (euros per kg), while for SSS, the cost is between 0.11 and 0.14 euros per kilogram.…”
Section: Regional Benefits Of Sssmentioning
confidence: 93%
“…For road haulage, the generalized cost from Leige to Riga, St. Petersburg, and Tallinn is about 80, 105, and 97 (in euros per ton), respectively, while for SSS, the corresponding cost is 69, 101, and 79 euros per ton, respectively. In a similar study, Galati, et al [27] identified that from Jaen to main Italian cities, the unit cost for road haulage is between 0.14 to 0.20 (euros per kg), while for SSS, the cost is between 0.11 and 0.14 euros per kilogram.…”
Section: Regional Benefits Of Sssmentioning
confidence: 93%
“…Using such data in Tableau Desktop software, the geographical locations of institutions that have contributed to research on modal shift were mapped, as shown in Figure 3. Paixao and Marlow (2002) Literature research Europe Brooks and Frost (2004) Literature research Canada Sanchez and Wilmsmeier (2005) Literature research Central America Paixao and Marlow (2007) Literature research Europe Baird (2007) Literature research Europe Medda and Trujillo (2010) Literature research Europe Baindur and Viegas (2011) Literature research Europe Douet and Cappuccilli (2011) Literature research Europe Aperte and Baird (2013) Literature research Europe Suárez-Alemán 2016Literature research Europe Mathematical models Ng (2009) Integer programming Europe Chang et al (2010) Linear programming model South Korea Tsamboulas, Moraiti, and Vlahogianni (2010) Probabilistic 2012Case study USA Hjelle 2014Case study Europe Bergqvist, Turesson, and Weddmark (2015) Case study Europe Galati et al (2016) Case Study Europe Mixed methods D' Este and Meyrick (1992) Interviews and stated preference survey Australia D'Este (1992) Literature research and stated preference survey Australia Becker, Burgess, and Henstra (2004) Case study, literature research and interviews Europe Bergantino and Bolis (2008) Interviews and adaptive stated preference technique Europe Brooks and Trifts (2008) Survey and discrete choice methods Canada Perakis and Denisis (2008) Literature research and SWOT analysis USA Garcia-Menendez and Feo-Valero (2009) Interviews and disaggregate behavioural model Europe Lee, Hu, and Chen (2010) External cost models and Interviews Taiwan Bendall and Brooks (2011) Literature research and interviews Australia, Canada, USA Notteboom 2011Survey and comparative price analysis Europe Puckett, Hensher, Brooks, and Trifts (2011) Survey and generalised mixed logit model Canada, USA Baindur and Viegas (2012) Case study, interviews and simulation model The size of the red circles in…”
Section: Distribution By Geographical Area Of Focusmentioning
confidence: 99%
“…The added value of those studies is that their analyses included the quantified values of attributes of service quality, including frequency and reliability. By using the updated values in the cost model developed byMorales-Fusco et al (2012),Galati et al (2016) compared different transportation scenarios (i.e. road-only transport, road transport with Accompanied-SSS, and road transport with Unaccompanied-SSS) for olive oil distribution from Spain to Italy and found that road-only transport was the most expensive option.Focusing on the East Adriatic and Ionian Sea region, Tsamboulas et al (2015b) identified prospective intermodal SSS links that are financially competitive under the European Commission's MoS programme Martell et al (2013).…”
mentioning
confidence: 99%
“…Some recent contributions to the theme provide evidence about the links between the olive oil sector and other industries such as tourism [40,41]. Different opportunities emerge along with the increasing trend in tourism-based initiatives in relation to olive oil [42].…”
Section: Oleotourismmentioning
confidence: 99%